2001
DOI: 10.1264/jsme2.2001.234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Harmful Dinoflagellate Heterocapsa circularisquama Cells on the Growth of Intracellular Bacteria.

Abstract: The red tide dinoflagellate Heterocapsa circularisquama Horiguchi has intracellular bacteria. The isolation and cultivation of these bacteria were attempted for three-clonal strains of H. circularisquama (HY9423, HA92-1, and HU9433) using various culture media containing cell components of the host alga prepared by homogenization and heat killing, in addition to different organic materials (peptone and extracts). Only one intracellular bacterium of the bacterial population UBb in H. circularisquama strain HU94… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Most intracellular bacteria need living alga for their growth and survival, except the intracellular bacteria of H. circularisquama strain HU9433 (Maki & Imai 2001b). Only bac-F of strain HU9433 is culturable on the medium for heterotrophic bacteria, but those of strains HA92-1 and HI9428 are not (data not shown).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Most intracellular bacteria need living alga for their growth and survival, except the intracellular bacteria of H. circularisquama strain HU9433 (Maki & Imai 2001b). Only bac-F of strain HU9433 is culturable on the medium for heterotrophic bacteria, but those of strains HA92-1 and HI9428 are not (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, H. circularisquama would spontaneously maintain 2 specific bacteria, by supporting their growth and survival (Maki & Imai 2001b). It is suggested that the relationship between H. circularisquama and 2 ribotypes of bacteria is considerably close and should be termed as endosymbiosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation